MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH - Sonny Muhammad Ikhsan Mangkuwi; Masyrida Masyrida; Muhammad Bahtiar; Nora Silvia (CV. Adiba Aisha Amira, 2025)
According to this study, the final decision is made by the foundation's leadership after school stakeholders participate in the preparation of the RAPBS (Annual Budget Plan) for education at the end of each year. The organisational structure, headed by the school principal and the foundation chairperson, functions as a mechanism for allocating funds for education. School activities, capital expenditures, purchases of products and services, and human resource development—particularly for teachers—are all funded by this budget. The Indonesian Community Care Foundation and the education department conduct oversight, while the School Committee and the foundation are responsible. In educational institutions, effective, transparent, and open financial management is recognised as having a positive impact on improving educational standards.